Accessible tourism in Andalusia. Emerging tourism product - Jurado-Almonte, Jose Manuel (Revista de Estudios Andaluces, 2014)
Despite the progress in universal accessibility and integration of people with sensory or locomotor disability, much remains to be done, especially in regards to accessible tourism. A growing phenomenon of enormous potential and economic and social opportunities. However, there have been innovative public and private experiences of destinations and facilities for public use and tourist vocation especially focused on this large and diverse group which are interesting to highlight because of their business and social transcendence. Also, it is a new typology or model, accessible tourism, with notable conceptual uncertainties and scantily studied from Geography. Our attention will be focused this time in Andalusia, although its analysis is inseparable from the scales of Spain and Europe.